INFRAÇÕES E INOVAÇÕES EM O ENCOBERTO, DE NATÁLIA CORREIA - Troczinski, Luiza Oliveira (2021)
This research work aims to study the play O Encoberto, by Natália Correia (1923-1993), in which different aesthetics and theatrical language elements are incorporated by the author as a way to expand the theatrical genre characteristics, subverting the concept of a well-written play, while reconstructing the traditional references of the Sebastianist myth by transposing Sebastian from a historical figure to a theater comedian one. The analysis develops from the reading considerations proposed by Vincent Jouve (2002), from the voids and denials theory by Wolfgang Iser (2001), within the Reader-Response Criticism; Patrice Pavis’s (2015) contributions, regarding theatrical language, are also addressed, Martin Esslin’s (2018) The Theater of the Absurd, Bertold Brecht’s (1978) Epic Theater and Valentin Volóchinov’s (2018) dialogism, among other scholars studying theater and Sebastianism itself. Assuming that the play reader reads several codes simultaneously, this work aims to demonstrate, with O Encoberto, that the play is presented full of outward elements, as well as theatrical-writing specific elements, which need to be rescued so that the understanding of the text as a communication element is established as a dialogic relationship.